2003
DOI: 10.1093/ajcn/78.1.123
|View full text |Cite
|
Sign up to set email alerts
|

Soy protein with isoflavones has favorable effects on endothelial function that are independent of lipid and antioxidant effects in healthy postmenopausal women

Abstract: Daily consumption of soy protein with isoflavones can result in positive vascular effects that are independent of lipid and antioxidant effects in healthy postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
135
1
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(143 citation statements)
references
References 52 publications
3
135
1
4
Order By: Relevance
“…This observation (Nikander et al, 2003), in conjunction with the effect observed with formononetin-rich but not biochanin-rich tablets (Teede et al, 2003) suggests that daidzein may be the primary isoflavone responsible for modulating adhesion molecules. Alternatively, ability to convert daidzein to equol could be a factor in the effectiveness of the formononetin-rich preparation; however, in the present study as well as two others with results divided by equol production (Steinberg et al, 2003;West et al, 2005), no differences were found in the responses of equol producers compared with nonproducers.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…This observation (Nikander et al, 2003), in conjunction with the effect observed with formononetin-rich but not biochanin-rich tablets (Teede et al, 2003) suggests that daidzein may be the primary isoflavone responsible for modulating adhesion molecules. Alternatively, ability to convert daidzein to equol could be a factor in the effectiveness of the formononetin-rich preparation; however, in the present study as well as two others with results divided by equol production (Steinberg et al, 2003;West et al, 2005), no differences were found in the responses of equol producers compared with nonproducers.…”
Section: Discussioncontrasting
confidence: 82%
“…The present study and the three studies reporting no effects (Blum et al, 2003;Steinberg et al, 2003;West et al, 2005) were relatively short (6 weeks); it is possible a longer duration is required for a decrease to be observed. These studies similarly incorporated B25 g day À1 of isoflavone-rich soy protein; a higher dose may be needed to achieve the threshold plasma isoflavone concentration for an effect on adhesion molecules.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Fourteen of the remaining 19 RCTs had a parallel design while five (Evans et al, 2007;Greany et al, 2004;McVeigh et al, 2006;Steinberg et al, 2003;Thorp et al, 2008) had a cross-over design. All subjects (n=1,947) who entered data analysis had normal or moderately elevated blood LDLcholesterol concentrations at baseline.…”
Section: Scientific Substantiation Of the Claimed Effectmentioning
confidence: 99%
“…In eight of the 19 RCTs, background diet was not assessed and possible confounding effects resulting from differences in background diet between the intervention and the control were not taken into account. Dietary intake was assessed in the remaining 11 studies, either by food frequency questionnaires (Allen et al, 2007;Crouse et al, 1999;Kreijkamp-Kaspers et al, 2004;Thorp et al, 2008) or by three-day dietary records (Baum et al, 1998;Greany et al, 2004;McVeigh et al, 2006;Santo et al, 2008;Steinberg et al, 2003;Teixeira et al, 2000;Van Horn et al, 2001). …”
Section: Scientific Substantiation Of the Claimed Effectmentioning
confidence: 99%